Remote activation of the Wnt/β-catenin signalling pathway using functionalised magnetic particles. - Michael Rotherham; Alicia J El Haj (PLoS ONE)
Wnt signalling pathways play crucial roles in developmental biology, stem cell fate and tissue patterning and have become an attractive therapeutic target in the fields of tissue engineering and regenerative medicine. Wnt signalling has also been shown to play a role in human Mesenchymal Stem Cell (hMSC) fate, which have shown potential as a cell therapy in bone and cartilage tissue engineering. Previous work has shown that biocompatible magnetic nanoparticles (MNP) can be used to stimulate specific mechanosensitive membrane receptors and ion channels in vitro and in vivo. Using this strategy, we determined the effects of mechano-stimulation of the Wnt Frizzled receptor on Wnt pathway activation in hMSC. Frizzled receptors were tagged using anti-Frizzled functionalised MNP (Fz-MNP). A commercially available oscillating magnetic bioreactor (MICA Biosystems) was used to mechanically stimulate Frizzled receptors remotely. Our results demonstrate that Fz-MNP can activate Wnt/β-catenin signalling at key checkpoints in the signalling pathway. Immunocytochemistry indicated nuclear localisation of the Wnt intracellular messenger β-catenin after treatment with Fz-MNP. A Wnt signalling TCF/LEF responsive luciferase reporter transfected into hMSC was used to assess terminal signal activation at the nucleus. We observed an increase in reporter activity after treatment with Fz-MNP and this effect was enhanced after mechano-stimulation using the magnetic array. Western blot analysis was used to probe the mechanism of signalling activation and indicated that Fz-MNP signal through an LRP independent mechanism. Finally, the gene expression profiles of stress response genes were found to be similar when cells were treated with recombinant Wnt-3A or Fz-MNP. This study provides proof of principle that Wnt signalling and Frizzled receptors are mechanosensitive and can be remotely activated in vitro. Using magnetic nanoparticle technology it may be possible to modulate Wnt signalling pathways and thus control stem cell fate for therapeutic purposes.